The psychology of art and the evolution of the conscious brain. - Raymond, Jane E.; Pollux, Petra M. J. (Visual Cognition, 2005)
Solso, R. L. (2003). The psychology of art and the evolution of the conscious brain. Cambridge, MA: MIT Press. Pp. 264. ISBN 0-262-192484-8. Price: $45.00/£29.95 (hbk).This book, with its intriguing title, explores the general notion that the appreciation of visual art can be understood using basic principles of human psychology and its more modern derivative, cognitive neuroscience. It specifically attempts to link the evolution of conscious thought with the evolution of art and to link the psychological components of consciousness such as attention, awareness, memory, and emotion, with art appreciation. The basic thesis is that when humans evolved conscious awareness, they were able to make conscious associations between pleasurable experiences and stimuli. This awareness formed the basis for a sense of aesthetics that empowered people to create and, then, to value art. Inherent in the thesis presented here is the notion of a common universal sense of aesthetics. Solso sees this existing as a result of a common set of brain mechanisms that have been shaped by evolution.The main limitation of Solso's perspective is that the appreciation of art is as much about the diversity of preference as it is about a universal aesthetic. The belief that all humans respond to and evaluate images in the same way has to be pitted against the obvious fact that people differ in what they value as art and why they value art. Because of the massive complexity of the human brain, cognitive neuroscience has been preoccupied with describing and understanding those aspects of human thought and behaviour and their neurobiological underpinnings that are common to us all. Indeed, it is a widespread assumption amongst cognitive neuroscientists that only when the basic, universal mechanisms are described and understood can we make progress on comprehending the nature of our cognitive diversity. With this backdrop, Solso has placed his foot squarely in the universal aesthetic camp and given only lip service to the role of human diversity in art appreciation.For me, Solso's attempts to use modern cognitive neuroscience to account for art appreciation fails to deliver anything strikingly new. This is perhaps because the cognitive neuroscience concepts are familiar to me and the insights he provides on why we appreciate art seem straightforward extrapolations of established, although in places out-of-date, ideas. However, to a person naïve to cognitive neuroscience and its general perspective these ideas may seem quite novel and exciting.The book, written in a colloquial style, shifts between the elementary and the somewhat more complex. Someone completely naïve to psychology and cognitive neuroscience might not find it understandable in places; for the student of psychology, the book seems directed at an undergraduate level. On the other hand, the treatment of art seems very elementary and uses a conventional set of artworks (almost exclusively paintings) to illustrate points. For a book about visual art, the pictures and diagrams are decidedly unexciting. There are few colour plates and the diagrams could be part of any conventional elementary text in Psychology.The book begins with a tutorial on looking at art. Here, Solso proposes that seeing art occurs as two levels. The first is a “nativitistic”, sensory level wherein the “bottom-up” mechanics of vision are marshalled to the task of visual analysis. This stage, he proposes, is “independent of conscious control” and we are “enslaved by photons and physiology”. The assumption is that we are all the same and we all “see” a work of art identically at this stage. Then he proposes a second “directed”, top-down stage of perception based on learning and experience, one that makes use of selective attention and consciousness. He proposed that this stage produces a perception of art that is highly personal and individual because it is at this stage that semantics, emotion, and personal relevance come into play. However, this general division of the mental processes produced in response to seeing art into a nonconscious bottom-up stage and a consciously controlled, top-down stage is based on a dated, feedforward view of perceptual processing. Here, and at several other points in the book, there is an uneasy, uncertain sense of where in this two-stage scheme consciousness actually comes into play and where individual differences in art appreciation might emerge. At the end of this tutorial, he states that there is no place within his two-stage model to explain “the profound and enigmatic effect art has on people”. This is a real disappointment because this should be what a thesis on art and perception is about. One wonders if the general ideas presented here could be used equally well to explain our interpretation of an everyday advertisement or an ordinary (not particularly artistic) scene. Psychology already has good theories and ideas about how humans interpret complex scenes and this book provides no advance on these.In the first chapter, entitled “Art and the rise of consciousness” Solso outlines his “model” of awareness, pointing to “the five facets of consciousness”. These are attention, arousal, memory, emotion, and the notion that brain structures mediate consciousness (something he calls architecture). The role of each is described in an elementary fashion. Unfortunately, a model of consciousness is not really presented. Moreover, the theoretical notions that form the basis for each “facet” seem outdated and, to the experimental psychologist, overly simple to be of significant interest.Chapter 2 explores human evolution. This is an interesting chapter for those uninformed about this but some of the inferences made involve far-fetched, unsubstantiated extrapolations from studies of anthropological evolution to neural mechanisms. There are numerous contradictions. How can a chapter on human evolution also contain the following statement: “In the African crucible of human creation, God reached down into the mud and from it created a man and a woman” (p. 64)? The discussion of the brain's evolution is used to introduce some concepts about brain organization (e.g., visual modules, memory systems), but, as in the preceding chapter, the concepts are too simple to be of interest to experimental psychologists and my guess is that they are too haphazard to be of much use as an introduction to brain mechanism for the layman. The third chapter, “Art and vision” suffers along the same lines. Here, Solso provides a piecemeal, introductory-level meander through the basics of visual science. There are multiple irrelevant digressions and the application of visual science to art is conventional. However, there are some interesting nuggets of information (especially about colour) and, for those naïve about visual processing, this chapter is probably of value. It assumes that low-level visual processing is immune from the influences of high-level semantic and emotional interpretation and that visual processing is fully feedforward. As such it seems outdated and uninformed by the exciting current notions that rapid parallel processing involving brain areas that contribute to emotional, motor, semantic, and executive control functions can modulate even very early visual processing.Next there is a chapter developing the notion that consciousness emerged from evolutionary pressures. This chapter, “Art and the brain”, explores brain organization. However, as in the preceding chapters, the text wanders. We are given a cursory introduction to neurons, neuroscience imaging, parallel distributed processing, reaction time paradigms, semantic priming, localization of function, and a discussion of the division of the extrastriate visual pathway into ventral and dorsal routes. Here, taking visual modularity to an extreme, Solso suggests that artworks could eventually be classified by the brain area each activates, rather than the “subjective” categorization of art scholars. He goes so far as to extrapolate from a recent brain imaging study to say that “the processing of realistic objects takes place in different regions of the brain than the processing of ‘abstract’ objects. It is plausible to extend this argument to surrealistic forms of art which, I would hypothesize, perform out of another cerebral theatre” (p. 129). Such a view denies the well-established interactivity of brain structures and seems naïve for a book offering a cognitive neuroscience theory of art. Contradicting his own point of view, he then acknowledges that individual, high-level interpretation of art involves a “tangle of meandering streams aroused by complex thoughts” (p. 131). Solso is pessimistic that neuroscience can ever address our complex responses to art. Perhaps this is because he sees neuroscience as a brain-mapping exercise rather than the investigation of process and mechanism. Once again we are left with a set of ideas of how all humans might process any (ordinary?) image and no real insight into how individuals interpret images, especially art images, in meaningful and emotive ways.One of the most interesting and more up-to-date chapters in this book is the one on faces. Solso reviews the evolution of faces in mammals and then discusses their importance in art. He reviews some of the relevant neuroscience and behavioural studies of face processing, espousing the “faces are special” view. This chapter is again somewhat piecemeal, going into considerable depth on specific studies of face distortion adaptation yet neglecting a whole literature on the seemingly relevant area of face expression interpretation. He finishes this section with the proposal that we evolved neural networks, so called “aesthetic cells”, responsive to attractive things, faces among them. He proposes that these cells are “innate (though with cultural ‘tuning’), are pragmatic (for survival purposes), are universal, are sexual, and play a vital role in social interactions ... [and] as a by-product gave humankind art” (p. 167). For me this is where Solso's thesis becomes cloudy. If the so-called aesthetic cells are “universal”, then why are people so different in their preference for art? At several points in the book he suggests that individuality in response to art stems from late, high-level, semantic interpretation, but he never connects this later stage with the so-called “aesthetic cells” presumably necessary for art appreciation.There are two chapters dealing with illusions, a seemingly obligatory component of a book on psychology and art. After discussing perceptual veridicality, the standard visual illusions are described with examples from works of art. Perceptual constancies, illusions of depth, motion, and size are discussed. The monocular and binocular cues to depth are reviewed as in any introductory psychology text, with the addition of examples from drawing and photography. In this section there is again an emphasis on the notion of a universal aesthetic, one that is derived from visual mechanisms. He invents a concept called species-specific empathic perspicuity, which “is the tendency of one member to tune into the thoughts of another by reason of having similar perceptual-cognitive experience ... Your percepts are universal; your reactions to art are the same as your neighbours; your thoughts are the same as mine” (p. 173). But, he says, derivation of meaning differs among people. So assuming meaning is related to thought we have an obvious contradiction. This contradiction is at the heart of what limits this book. The conflict between the universal and the individual response to art is confusingly presented and never resolved. Where and how consciousness comes into this conflict is also unclear.The last chapter concerns higher level cognition and its role in perception and art appreciation. At last there is a discussion of how semantic, contextual, and personal factors influence appreciation of art. Solso explores the cognitive concepts of schemata, prototypes, abstraction, canonical representation, and social cognition and their relationship with art. Unfortunately, this section is standard psychology simply applied to art. It could just as easily be applied to ordinary, everyday scenes. In the closing pages of the book, Solso describes what he sees as a level of art appreciation beyond semantic interpretation, something akin to emotion, perhaps, although this is not clearly articulated. “It is being at ‘one’ with the art; it is commingling a painting with universal properties of the mind; it is seeing one's primal mind in a painting” (p. 258). In stating this, Solso is once again asserting that art appreciation is based on universal principles that derive from a common brain structure.Although no one would doubt that all (healthy) human brains have much in common structurally and neurophysiologically, the obvious extension of Solso's idea is that we all respond to art in the same way. We do not. What Solso has missed is that along with the set of low-level, hard-wired visual mechanisms he refers to, the human brain evolved high-level, adaptive cognitive mechanisms to enable appropriate emotional, evaluative, cognitive, and motor responses to a wide range of stimuli. The way these mechanisms work may well be universal, but the information they work with is not. Consequently the mental events, both conscious and unconscious, that they generate in each of us will vary.For me a satisfying theory of art must deal with human diversity rather than focus on describing a universal response to art. It is much more likely that we are motivated to look at and create art because we want to know the individual who is the artist, whether a stranger or ourselves. We do not seek to strengthen our sense of the prototypical human, to recognize what is common among us, but rather to acquaint ourselves with diversity and thus enlarge our vision of humanity. In this way, I see Solso's emphasis on a universal aesthetic as narrow but, at the same time, fully reflective of the science on which he has developed his views. Clearly, a theory of art based on cognitive neuroscience that can balance a universal preference with human diversity of taste is a tall order. Perhaps it is premature to expect one, given our limited understanding of what makes us each different. Solso's work will no doubt stimulate thought and discussion of this interesting potential marriage of art and science in ways that will benefit both disciplines. Jane E. Raymond Centre for Cognitive Neuroscience, School of Psychology, University of Wales, Bangor, UKRobertson, L. C. (2003). Space, objects, minds, and brains. Hove, UK: Psychology Press. Pp. 272. ISBN: 1-84169-0422. Price: £34.99 (hbk).This book addresses important questions about the relationship between spatial representation, spatial awareness, and perception of objects in the external world. The book has a strong neuropsychological emphasis, and illustrates how creative testing of one unique patient (RM) can address key issues in the study of space and object perception. Several of the author's ideas are argued throughout the book. One claim is that attentional mechanisms respond to space-based frames of references that organize objects into hierarchical structures. The second claim emphasizes the crucial role of the dorsal stream in processing explicit spatial knowledge, required for locating objects in the external world.In the first chapter the author draws upon her own experience in neuropsychological assessment of patients with Balint syndrome, unilateral neglect, and integrative agnosia to describe how perception of the external world can be affected when perception of space is disrupted. The chapter also introduces one of the central ideas in this book that object-based neglect observed in unilateral neglect is space-based, where the part of space that is neglected depends on the spatial reference frame that is selected to guide allocation of attention. Chapter 2 provides an overview of the literature on the properties of spatial reference frames. The chapter starts with a discussion of the critical components for establishing object-centred spatial frames of reference (e.g., origin, sense of direction, orientation, and unit size) and continues with a discussion of how these properties are affected in several neuropsychological phenomena described in Chapter 1.The third chapter addresses the notion that different spatial frames of reference can guide attention in selection of locations or regions of space. The argument is partly built upon evidence from studies where the viewer frame and scene-based frame (defined by the coordinate system of the stimulus display) are dissociated through rotation, or where fixation and attention are dissociated by spatial cueing. The chapter also includes a section on selection of local and global frames of references (spatial resolution) and discusses the notion that an “attentional print”, defined as the spatial scale most recently attended to, primes selection of the spatial reference frame in a subsequent trial.The third chapter provides the author's account for several object-based attentional effects. The first section of this chapter specifies differences between object- and location-based attentional effects in rotating displays (IOR), and in static displays where within- and between-object (exogenous) cueing effects can be compared. The author strongly advocates here that IOR in rotating displays (both to the object and the cued location) reflects spatial updating of locations within the display-based spatial reference frame. This is inferred from the finding that IOR is only observed when spatial relations between objects remain the same during rotation. Although this finding is supportive of her claim, differential attentional effects to the cued location and the targeted object in rotating displays remain underspecified in this account. It is further argued that costs (IOR) are associated with the inhibition of locations only and are not sensitive to object structure, unlike facilitation effects (e.g., boundaries). This interpretation can account for the pattern of results found by Robertson and Beuche when comparing within- and between-object exogenous cueing effects. The absence of spreading inhibition across object surfaces is not, however, consistently supported in the literature. The remainder of the chapter provides a reinterpretation of object-based neglect in terms of the multiple frame account, introduced in Chapter 1. Although the author admits that a few findings remain problematic for the multiple frame account, the discussion is interesting and thought provoking.Chapter 5 discusses the role of the ventral and dorsal processing stream in processing of space. The author proposes that the dorsal stream is involved in explicit spatial knowledge, but not in implicit spatial encoding. Below awareness, spatial information may be processed in several different structures, such as the ventral medial premotor cortex/putamen (eye–hand coordination), superior colliculus/frontal eye field (eye-movement control), hippocampal place cells (spatial memory), precentral sulcus, and in the ventral stream. Evidence is partly provided in a detailed description of spared and impaired spatial encoding of a patient with Balint syndrome (RM). Despite chance performance on tasks measuring explicit spatial knowledge, RM showed evidence of encoding of global form, spatial relationships between two objects, and some evidence of encoding of more complex spatial relations when tested implicitly. The author's ideas about the role of the ventral stream are discussed against a model proposing that the ventral stream represents spatial structures of objects that are sufficient to support awareness. Both supporting and contradicting evidence from two Balint patients is discussed for explicit access to spatial relations within objects (parts of objects), including the possible influence of top-down processes on the patients' ability to locate parts of objects.In Chapter 6 the author argues that explicit spatial knowledge is required for binding surface features, such as shape, colour, and motion. Interesting evidence is reported from a series of studies investigating visual search performance of RM, which was characterized by a high percentage of illusory conjunctions. It is further proposed that feature binding and individuation of objects relies on the integrity of the parietal lobes, although the debate about the specific functions of the parietal cortex in feature binding is left unresolved.Chapter 7 describes an integrative analysis of the relationship between spatial awareness and perception, as revealed by spatial deficits associated with brain injury (bilateral and unilateral parietal lesions, and lesions to the ventral right hemisphere). Chapter 8 includes a summary of all chapters and several unresolved issues/questions are identified for future research.In general this book provides an interesting view on the relationship between awareness and spatial processing. As mentioned in one of the reviews on the cover, the book “reads like a novel”. It is therefore not only important for researchers in the field of space and object perception, but also accessible to undergraduates who have a particular interest in cognitive neuroscience. Petra M. J. Pollux University of Lincoln, UK